Use of space and dispersal ability of a flagship saproxylic insect: a telemetric study of the stag beetle (Lucanus cervus) in a relict lowland forest. Issue 1 (10th September 2017) - Tini, Massimiliano; Bardiani, Marco; Chiari, Stefano; Campanaro, Alessandro; Maurizi, Emanuela; Toni, Ilaria; Mason, Franco; Audisio, Paolo A.; Carpaneto, Giuseppe M.
Abstract: The stag beetle, Lucanus cervus (Linnaeus, 1758) (Coleoptera: Lucanidae), is a flagship species for the conservation of European old‐growth forests. Despite its popularity and many studies conducted, the lack of knowledge of its habits and ecological requirements leads to difficulties in locating the species in the field and to provide information for suitable planning conservation actions suitable for the species. In order to gather information on dispersal ability and space use, a radio‐telemetry study was conducted in a relict floodplain forest surrounded by intensively cultivated land. During 2014 and 2015, from May to July, 55 beetles (34 males, 21 females) were radio‐tagged, and 9 of these (7 males, 2 females) were telemetered immediately after the emergence from their development sites, by means of emergence traps. The use of radio‐telemetry allowed to detect the oviposition sites and to study the first part of the adult life, when they resulted to be more active. Males were more prone to disperse than females but the home range size did not differ between the sexes. Dividing the season in three intervals, the most active individuals were recorded during the first and the second ones (first and second half of June).